Mixing behavior of p-terphenyl-3, 5, 3′, 5′-tetracarboxylic acid with trimesic acid at the solid–liquid interface. Issue 45 (15th November 2021) - Li, Wei; Chen, Jianbin; Zhang, Chengdong; Li, Yudie; Wan, Lijia; Chen, Xiaoling
Abstract : The molecular self-assembly of carboxylic acid molecules on a solid surface plays an important role in understanding the nanoscale-precision construction of functional patterns. Abstract : The molecular self-assembly of carboxylic acid molecules on a solid surface plays an important role in understanding the nanoscale-precision construction of functional patterns. In this study, the mixing behavior of p -terphenyl-3, 5, 3′, 5′-tetracarboxylic acid (TPTC) and trimesic acid (TMA) on a highly oriented pyrolytic graphite surface was studied by scanning tunneling microscopy (STM). The STM images show how the presence of a small percentage of TPTC molecules adsorbed onto TMA molecules can drastically change the on-surface self-assembly behavior of aromatic tetracarboxylic acid by initiating the nucleation and growth of a different polymorph. Molecular mechanics and density functional theory simulations of the adsorption energy and the additional stabilizing energy, induced by hydrogen bonds during assembly formations, provide insights into the relative stability of different assembled structures. Moreover, STM-based "nanoshaving" was conducted to confirm that the template layer underneath the second layer is indeed a random network.